Living with floods – Household perception and satellite observations in the Barotse floodplain, Zambia. (August 2017) - Cai, Xueliang; Haile, Alemseged Tamiru; Magidi, James; Mapedza, Everisto; Nhamo, Luxon
Abstract: The Barotse Floodplain, a designated Ramsar site, is home to thousands of indigenous people along with an extensive wetland ecosystem and food production system. Increasingly it is also a popular tourist destination with its annual Kuomboka festival which celebrates the relocation of the king and the Lozi people to higher ground before the onset of the flood season. This paper presents an integrated approach which cross validates and combines the floodplain residents' perceptions about recent floods with information on flood inundation levels derived from satellite observations. Local residents' surveys were conducted to assess farmers' perception on the flooding patterns and the impact on their livelihoods. Further, a series of flood inundation maps from 1989 to 2014 generated from remotely sensed Landsat imagery were used to assess the recent patterns of floods. Results show that the floodplain has a population of 33 thousand living in 10, 849 small permeant or temporary buildings with a total cropland area of 4976 ha. The floodplain hydrology and flooding patterns have changed, confirmed by both surveys and satellite image analysis, due to catchment development and changing climate. The average annual inundated areas have increased from about 316 thousand ha in 1989–1998 to 488 thousand ha in 2005–2014. As a result the inundated cropland and houses increased from 9% to 6% in 1989 to 73% and 47% in 2014, respectively. The timing of the floods has also changed with both delaying and early onset happening more frequently. These changes cause increasing difficulties in flood forecast and preparation using indigenous knowledge, therefore creating greater damages to crops, livestock, and houses. Current floodplain management system is inadequate and new interventions are needed to help manage the floods at a systematic manner. Highlights: Cycles and impacts of the historical floods in the Barotse floodplain were assessed. Remote sensing and residents' perceptions were combined to improve results. The flood patterns are changing and more difficult to predict and adapt. Modern technology with indigenous knowledge improve the acceptance and reliability.